2005
DOI: 10.1620/tjem.207.99
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid 1 Receptor Antagonist, AM251, Prolongs the Survival of Rats with Severe Acute Pancreatitis

Abstract: It has recently been recognized that anandamide (arachidonylethanolamide), which is an endogeneous-cannabinoid (endocannabinoid), mediates septic shock. Cannabinoid means a mind-active material in cannabis (marijuana). Anandamide is mainly produced by macrophages. Cannabinoid 1 (CB1) receptor, which is one of the cannabiniod receptors, is also known to mediate hypotensive shock. The role of endocannabinoids in the progression of acute pancreatitis is unclear. The aims of this study are to clarify their relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…This result was attributed to modulation of ␤-adrenergic vasodilation, rather than suppression of a direct vasodilator effect by endocannabinoids (Gardiner et al, 2005). Interestingly, in a recent study, Matsuda et al (2005) demonstrated that AM251 improved mean arterial pressure and survival rate in models of severe acute necrotizing pancreatitis without affecting inflammatory changes, which suggests the involvement of cardiac or vascular CB 1 receptors in the hypotension associated with this condition.…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was attributed to modulation of ␤-adrenergic vasodilation, rather than suppression of a direct vasodilator effect by endocannabinoids (Gardiner et al, 2005). Interestingly, in a recent study, Matsuda et al (2005) demonstrated that AM251 improved mean arterial pressure and survival rate in models of severe acute necrotizing pancreatitis without affecting inflammatory changes, which suggests the involvement of cardiac or vascular CB 1 receptors in the hypotension associated with this condition.…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 99%
“…Circulatory Shock. The profound hypotension that can be elicited through pharmacological activation of CB 1 receptors (Lake et al, 1997a) triggered numerous studies to investigate the role of the endocannabinoid system in the hypotension associated with various forms of shock, including hemorrhagic (Wagner et al, 1997;Cainazzo et al, 2002), endotoxic (Varga et al, 1998;Wang et al, 2001;Liu et al, 2003a;Bá tkai et al, 2004a;Gardiner et al, 2005;Kadoi et al, 2005), and cardiogenic shock (Wagner et al, 2001a, and the shock associated with necrotizing pancreatitis (Matsuda et al, 2005). Initial studies demonstrated that the putative CB 1 receptor antagonist SR141716 prevented or reversed the hypotension associated with hemorrhagic, endotoxic, and cardiogenic shock (Wagner et al, 1997(Wagner et al, , 2001aVarga et al, 1998).…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…CB1 receptor activation has shown to induce fibrosis while activation of CB2 receptor is linked with antifibrogenic effects in the pancreas (1,20). Matsuda et al (24) showed that down regulation of endocannabinoid system by AM251 (a CB1 receptor inhibitor) improved survival in rats with severe AP. This finding was later confirmed by another study (25).…”
Section: Discussionmentioning
confidence: 99%
“…And it has been reported that they are anatomically distributed in the spinal dorsal horn that is involved in the conduction and control of pain. A lot of findings from research using laboratory animals revealed that cannabinoid receptors typically show analgesic action 3 . A cannabinoid receptor agonist injected in the meningeal space alleviated hyperalgesia and allodynia in neuropathic and inflammatory pain models, and D9-tetrahydrocannabinol (THC) and anandamide (AEA), which were injected into the abdominal cavity, reduced pain from excitotoxic pressure on the plantar surface in animal models of arthritis.…”
Section: Introductionmentioning
confidence: 99%